Teachers’ Perception and Attitude toward the Use of Handheld Technologies in the Instructional Process in Secondary Schools in Zamfara State, Nigeria - Shehu, Suleiman Abdullahi; Osuji, Celestina Nnenna (Faculty of Natural and Applied Sciences Journal of Mathematics, and Science Education, 2024)
Handheld Technologies are numerous and they range from mobile phones, e-book readers, laptops, and personal digital assistants (PDA), all the made mentioned have become teaching and learning tools over the time and they have great potential with respect to their uses in classroom settings and in outdoor learning. However, research conducted has showcased their uses for educational purposes but their quantitative study is not much. Therefore, the study investigated teachers' perceptions and attitudes toward the use of hand-held technologies for the instructional process in secondary schools in Zamfara state. The study highlights the need for a deliberate shift in focus and practice towards the used of handheld technologies in this digitized era, Therefore, the study examined some available handheld technologies used for instructional processes by teachers in secondary schools across the state, which aimed at finding out whether the teachers have access to such technologies for instructional usage and do they perceive their usefulness and ease of use of the technologies for instructional process. Similarly, it explores major inhibiting factors to the effective use of the available handheld technologies for the instructional process. In total, 788 out of 835 teachers were served with the questionnaire. Four research questions were answered. Standard deviation and mean scores statistical measures were used to answer the research questions. Some of the findings as regards teachers’ access are: laptops had the highest percentage of respondents with 635 (79.4%), follow by smartphones with respondents of 589 (60.6%). Cell phone had access respondents of 532 (50.4%); multimedia players had access respondents of 491(45.0%). Tablet pc had teachers' access respondents of 326(27.1%), while E-book reader had access respondent of 276(23.0%) and Netbooks among others. Some of the recommendations made include Professional development training for pre-service and in-service teachers in the state and an improved infrastructure that will support the use of handheld devices within the school system.